Physiological And Growth Responses Of Macoma Balthica (mollusca:pelecypoda) To Environmental And Genetic Factors, With Emphasis On A Hudson Bay Population Near Churchill - Lim, Shirley Siew-lee (Scholarship@Western, 1990)
Growth rate of most intertidal organisms generally declines in an upshore direction. However, Macoma balthica from 1.0m above mean low water (MLW) grew faster than those from MLW in Churchill (Hudson Bay). This anomaly was the focus of this study. The first objective was to determine if this phenomenon is widespread or localised. Results showed that the "Churchill phenomenon" was not present along the St. Lawrence River and the Bay of Fundy and was confined to sites along the coast of Hudson Bay east of Churchill to Cape Henrietta Marie on James Bay.;The second objective was to examine the effects of biotic and abiotic environmental factors on the growth rate and physiological responses of the Churchill clams. High tide Macoma were more heavily parasitized and grew faster than low tide ones and crawlers (more parasitized) grew faster than the buried (less parasitized) clams. Parasitic castration resulting in enhanced growth could be an explanation for these observations.;Results from transplant studies showed that Macoma transplanted from MLW to 1.0m above MLW grew at a rate similar to that of the high tide "residents", indicating that the phenomenon is probably influenced by local environmental conditions at the two tide levels rather than by genotypic differences. No positive correlation was detected between growth rate and degree of heterozygosity (scored for the enzymes PGM, PGI, MDH and LAP) in the clams from either tide level.;The Qdollar\sb{lcub}10{rcub}{dollar} of Macoma from both tide levels was 1.5, indicating a moderately temperature-dependent metabolism. Weight-standardized oxygen uptake was inversely related to the size of Macoma. Low tide Macoma consumed more oxygen than high tide clams. This implies that high tide clams have greater metabolic efficiency: this energy "saved" may be used to further enhance their growth.;Contrary to expectations, low tide clams were able to withstand cold stress better than high tide clams in the laboratory. Low tide Macoma burrowed deeper into the substratum than ...